The Relationship Between Indoor Air Quality and Student Productivity in the Era of Hybrid Learning - Hasnawati; Eka Cahya Muliawati (CV. Get Press Indonesia, 2025)
The post-pandemic shift in education has accelerated the adoption of hybrid learning, which integrates both online and face-to-face instruction. Within this setting, indoor air quality (IAQ) plays a vital role in affecting students’ comfort, health, and productivity. This study investigates the relationship between IAQ and student productivity in the hybrid learning era. A quantitative approach was employed using a correlational survey design, involving several schools selected through purposive sampling. IAQ parameters measured included carbon dioxide (CO₂), temperature, relative humidity, and particulate matter (PM2.5 and PM10), using standardized digital instruments. Student productivity was evaluated via a structured questionnaire addressing concentration, focus, and academic performance. Descriptive analysis revealed that average levels of CO₂ (1185.6 ppm), PM2.5 (41.7 µg/m³), and PM10 (64.2 µg/m³) exceeded health standards, whereas temperature (28.3°C) and humidity (61.2%) remained within moderate limits. Productivity scores were in the fair-to-good range (average concentration 3.7; focus 3.5; academic achievement 77.8), with notable differences observed across classes. Pearson correlation analysis indicated significant negative associations between CO₂, PM2.5, and PM10 with all productivity indicators (p < 0.05). Multiple linear regression identified CO₂ (β = -0.412) and PM2.5 (β = -0.387) as the most influential factors in reducing student productivity. These results suggest that poor indoor air quality, particularly elevated CO₂ levels and fine particulate matter, is a key determinant that can impede the effectiveness of hybrid learning.